IMPACT OF SPECIFIC BIG-FIVE FACTORS ON BODY DYSMORPHIC DISORDER AMONG COSMETIC SURGERY PATIENTS - Arouj, Kehkashan; Zonash, Rabia (Pakistan Armed Forces Medical Journal, 2020)
Objective: To explore the predictive effect of big-five factors on Body dysmorphic disorder among cosmetic surgery patients.Study Design: Cross sectional design.Place and Duration of Study: Cosmetic centers of Rawalpindi and Islamabad, from Aug 2015 to Dec 2017.Methodology: Using correlation research design the sample of the present study consisted of 200 cosmetic surgery patients were taken from different. Big five inventory (BFI) and Dysmorphic concern questionnaire (DCQ) were used in the present study to assess specific personality characteristics and Body dysmorphic disorder among cosmetic surgery patients. Psychometric properties of selected instruments were explored for the present study.Results: The result was carried out using SPSS-21. The results of multiple linear regression showed that extraversion (β=-.22, p